The narrow road to the deep north, and other travel sketches - Bashō, Matsuo (Penguin, 1966)
Content: The records of a weather-exposed skeleton; A visit to the Kashima Shrine; The records of a travel-worn satchel; A visit to Sarashina village; The narrow road to the deep north